Transformasi Fungsi Tari Caping Gangsing Sebagai Identitas Budaya Desa Wisata Lerep Kabupaten Semarang - Kinanthi Setyaning Asih; Lesa Paranti (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study aims to describe the presentation form and analyze the functional transformation of the Caping Gangsing Dance as a cultural identity of Lerep Tourism Village, Semarang Regency. This research used a descriptive qualitative method with data collected through observation, interviews, and documentation. The informants included choreographers, dancers, tourism village managers, and community members involved in the development of the dance. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that the presentation form of the Caping Gangsing Dance consists of movement, musical accompaniment, makeup and costumes, properties, and performance structure that represent the agrarian life of the Lerep community. The caping property becomes a distinctive element that strengthens the dance identity, while the movements illustrate activities such as farming and mutual cooperation. The dance has also experienced functional transformation, from an educational medium introducing traditional games and local values to a cultural preservation medium, tourism attraction, village promotion media, and representation of community identity. This transformation indicates that Caping Gangsing Dance functions not only as a performing art but also as a cultural symbol that strengthens the image and identity of Lerep Tourism Village.